ALKITAB DALAM PERSPEKTIF HOMILETIKA YANG BERTEOLOGI - meriyana, meriyana; Sianipar, Rikardo P.; Carolina, Gressia (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2024)
A sermon serves as the platform through which a preacher conveys divine messages to the congregation. Thorough preparation and effective delivery constitute essential components of a sermon. The use of illustrations, testimonials, and the selection of Bible passages play a pivotal role in crafting a sermon. A preacher should strive to communicate a message that aligns with the will of God, rather than catering to the desires of the congregation or personal preferences. This research aims to explore the concept of the Bible from a theological homiletical perspective. The Bible is regarded as a divine revelation in which God manifests Himself. The Bible serves as the core source in sermon development. Unfortunately, not all preachers base their sermons on the Bible; at times, they rely more on personal thoughts or subjective experiences. This poses potential risks for the congregation since their faith should not be founded on the preacher's personal experiences. It is crucial for a preacher to comprehend the fundamental role of the Bible as a theological foundation in crafting sermons. The research methodology employed in this study is qualitative, with a focus on relevant literature and resources. The research findings affirm that sermons with theological depth should be anchored in the Bible. Such an approach is known as expository preaching. It can be concluded that as a preacher, the primary duty is to communicate God's message, not personal opinions. This is intended to build the congregation on the foundation of biblical truth and encourage transformation towards Christ.